INTERPRETASI PRICE EARNING RATIO DALAM PENILAIAN SAHAM SAHAM BLUE CHIPS DI BURSA EFEK INDONESIA - Azmir Ferdinansyah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2013)
Indonesian government gives obvious support for a progress of The Indonesian capital market because one of indicators that show a growth of Indonesian economy is a progress of capital market. Share is an object of investment, it has various characteristics that can be chosen by investors, one of them is Blue Chips share . So the research is needed for the Blue Chips shares by considering five variables to determine its value and the fairness of the value can be revealed as well. The purpose of this research is to know the valuation of share with price earning ratio approach (PER). The object of this research is a firm that include in the index valuation LQ 45 and known as a big, capable, and stable firm. So the result is not applicable for the firms that do not use Blue Chips. The population is 45 firms and 30 firmsÃ‚Â that use Purposive Sampling for the year 2006-2011 are taken as sample. Multiple Regression is used as model analysis. Clasical assumption test: BLUE has been done before, the prediction result is profit growth, dividend payout ratio, profit growth standard deviation, financial leverage, and return on equity can be analized. The analysis result shows : 1) partially there are two variables that has real impact on price earning ratio variability, and simultaneously all explanatory variables are influential ; 2) Financial leverage is explanatory variables that has the most influence on price earning ratio ; 3) The Blue Chips share in Indonesian Stock Exchange has not showed fair result based on Price Earning Ratio (PER) analysis. Other researchers can develop another variables besides those variables, because there is still 77% factors that can influence the Price Earning Ratio on this research.Key Word :Ã‚Â The Blue Chip Shares,Ã‚Â Fundamental Factor, Price Earning Ratio , The Indonesian StockÃ‚Â Ã‚Â Exchange Ã‚Â Ã‚Â